Risk Mitigation on Damage and Maintenance of Industrial Engineering Building Facilities at University XYZ Using The House of Risk (HOR) Method - Rahmawati, Fennyka; Asri, Maulida; Putra, Aldi Islammei Ananto (Jurnal Ilmiah Teknik Industri, 2025)
This study addresses the frequent damage to facilities in the Industrial Engineering Building at XYZ University, impacting classrooms, laboratories, and faculty rooms. Employing the House of Risk (HOR) method, this research identifies key risk agents and prioritizes mitigation strategies. Phase 1 of HOR focuses on risk identification and the calculation of Aggregate Risk Potential (ARP), while Phase 2 evaluates mitigation strategies using the Effectiveness to Difficulty Ratio (ETD). The findings highlight user negligence, lack of preventive maintenance, and poor procurement quality control as primary risk factors. Proposed mitigations include the implementation of Standard Operating Procedures (SOPs), targeted training, and enhanced maintenance scheduling. The results contribute to a systematic framework for improving the sustainability and reliability of campus facilities.